Ecological environment protection evaluation method based on mineral resource planning and its impact on land use - Yawei Hou; Ya Yang; Jiang Chang; Jing Peng (Humanities & Social Sciences Communications)
Abstract Mineral resource development is an important driving force for global economic progress, but its impact on land use has attracted increasing attention. The development of mining areas may lead to land degradation, loss of biodiversity, and decline in ecosystem services; therefore, assessing these influences is crucial for formulating sustainable development strategies. This study aims to evaluate the impact of mining area development on land use, quantify the changes in land use before and after development, and explore the potential effects of these changes on the environment and ecosystem. A comparative analysis method collects and analyzes land use data before and after mining area development, including land cover types, area changes, and land use conversion ratios. Based on statistical analysis, the degree of impact of development activities on land use is determined, and the significance of change is assessed using the P-value. The study involves variations in the area of construction land, farmland, grassland, and mining land, as well as the conversion of land cover types, such as farmland to construction land and grassland to mining land. The study also considers the potential impacts of these changes on ecosystem services and biodiversity. The research results reveal that the mining area development leads to a remarkable decrease in the area of farmland and grassland and a notable increase in construction and mining land areas. The results show that mining area development significantly impacts land use, which may lead to the decline of ecosystem service functions and the loss of biodiversity. These findings highlight the importance of a sustainable approach in the development of mining areas to reduce negative impacts on the environment. This study provides quantitative evidence for understanding the impact of mining area development on land use and a scientific basis for formulating effective environmental protection and sustainable development strategies.